2022
DOI: 10.3390/su14137909
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Digital Transformation Capability on Operational Performance

Abstract: With the changes in market environments and the development of digital technology, enterprises urgently need to develop the capability to adapt to profound changes in strategy and business processes. Some previous research regarded a digital marketing capability as a digital transformation capability, but other research explained the importance of digital competence to enterprises, from the perspective of resource allocation. However, they could not explain the phenomenon of enterprises on the usage of advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The mediating variables in this study also contribute to the increase or decrease in organizational performance which is influenced by factors such as technology readiness, strategic leadership, and organizational change. In addition, the results shown in this study have been able to confirm previous studies that have been revealed by (Kristian et al, 2023), (Blut & Wang, 2020), (Tetik, 2020), (Rosi D'Avila et al, 2021), (Supriharyanti & Sukoco, The Influence of Technology Readiness, Strategic Leadership, and Organizational Change on Organizational Performance in the Indonesian Navy 2023), (Darling & Venkitachalam, 2021), (Jensen, Øygarden, Mikkelsen, & Olsen, 2023), (Yu, Wang, & Moon, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…The mediating variables in this study also contribute to the increase or decrease in organizational performance which is influenced by factors such as technology readiness, strategic leadership, and organizational change. In addition, the results shown in this study have been able to confirm previous studies that have been revealed by (Kristian et al, 2023), (Blut & Wang, 2020), (Tetik, 2020), (Rosi D'Avila et al, 2021), (Supriharyanti & Sukoco, The Influence of Technology Readiness, Strategic Leadership, and Organizational Change on Organizational Performance in the Indonesian Navy 2023), (Darling & Venkitachalam, 2021), (Jensen, Øygarden, Mikkelsen, & Olsen, 2023), (Yu, Wang, & Moon, 2022).…”
Section: Discussionsupporting
confidence: 88%
“…Digital transformation (DT) is the application of cutting-edge digital technologies and solutions to modernise and enhance systems and processes, protocols, corporate culture and consumer engagement to meet and exceed the shifting requirements at business or strategic (Yu et al ., 2022). DT would entail integrating emerging technologies for digitally mature firms to solve their business concerns (Van Veldhoven and Vanthienen, 2022).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…DT is the application of cutting-edge digital technologies and solutions to modernise and enhance systems and processes, protocols, corporate culture and consumer engagement to meet and exceed the shifting requirements of business or strategy (Yu et al, 2022).…”
Section: Geographic Diversification and Export Performance: The Moder...mentioning
confidence: 99%